Family-Friendly Employment Policy Practices in the Malaysian Government and Selected Private Organizations - Ahmad, Aminah (2007)
This study examined the implementation of family-friendly employment policies in the government and selected private manufacturing organizations in Malaysia. Three broad categories of facilities were studied including work arrangements, family care benefits, and child care facilities and related benefits. Policy practices in the federal government were examined through document analysis and interviews with human resource personnel. Data from four private organizations were gathered using questionnaires and interviews with human resource managerial staff. Generally, the government has been more generous than the private organizations studied in providing family-friendly facilities. Overall, these organizations were still at the early stage of development of policies which could support the reconciliation of the demands of work and family life. The results imply the need to improve the family-friendly policy practices and the need to recognize the development of such policies as an important task for human resource development policy-makers.